Human Resource Development in Islam and the Management of Muslim Organizations - Yunus Walusimbi (Al Tijarah, 2023)
The practice of the HRD function has been found to have very important benefits to the organization and the employees involved. The HRD function is a very important strategic tool for the organization and when its practice is done the Islamic way it likely to come with a lot of benefits. HRD is Islam is about the fair treatment of employees by the employers. This study was about human resource development in Islam the often-forgotten concept in the management of Muslim organizations. The study examined the need for implementation of Islamic perspective of HRD in Muslim organizations and the need to find out the possible solutions to problem of failure to implement the Islamic perspective of HRD in Muslim organizations. The methodology employed was to examines the literature relating to human resource development, need for its implementation, related problems and the possible solutions to problem of failure to implement the Islamic perspective of HRD. The findings indicate that implementation of HRD in the Islamic perspective has enormous benefits like improved work performance moral build up. It was also found out that many Muslim organizations do not implement HRD with the Islamic perspective in their organization because they lack knowledge related to the same. It’s also found out that creating awareness about HRD practice in Islam will help to bring about the much-anticipated practice among Muslim organization. Keywords: Human resource Development, Islam, management, Muslim organization